Why Won’t My Patient Act Like a Jerk? - Baruch, Jay (The Hastings Center report, 2019)
I’m avoiding Mr. G’s room. I shouldn’t have read the emergency room notes from the other hospital, where this middle-aged man raised a stink about the wait. What type of person calls the triage nurse a bitch? From the timestamps on the electronic medical record notes, he stormed from that ER and drove his abdominal pain, vomiting, diarrhea, and discontent directly across town to us. I’m reminded of this oft-quoted aphorism from Sir William Osler: “The good physician treats the disease; the great physician treats the patient who has the disease.” It’s cited by medical educators as an invocation to never forget the humanistic heart at the center of clinical care. But what if the patient is a jerk? That I haven’t met Mr. G, only read briefly about him, doesn’t stop these ugly feelings from surfacing.